HARMONIZATION OF BUSINESS MODELS AND MARKETING STRATEGIES IN THE DIGITAL ECONOMY: CHALLENGES OF THE ENTROPIC ERA (Development Service Industry Management, 2025)
In today's digital economy, traditional business models are undergoing radical changes under the influence of new technologies, globalization, and the growing entropy of market processes. The main drivers of transformation are the development of high-speed Internet, mobile technologies, and the Internet of Things. Digital business models are no longer just a supplement to classical schemes — they set a new logic for creating value, forming relationships with consumers, and organizing processes within companies. At the same time, marketing strategies are also evolving. The classic 4P complex is transforming: the product is integrated with services, distribution is moving to digital channels, pricing is becoming dynamic, and promotion is based on personalization and data analytics. Harmonization of business models and marketing strategies is becoming critical. Only their coordinated development allows companies to effectively adapt to technological challenges and at the same time maintain consumer trust and loyalty. The article examines five key types of digital business models: platform, subscription, data-driven, IoT, and Direct-to-Consumer (D2C). For each model, both positive and negative examples of application in world practice are analyzed. The platform model, based on the network effect, is demonstrated by the cases of Airbnb and Amazon, which achieved global success thanks to building ecosystems and building trust. In turn, the example of eBay shows the risks of untimely adaptation of marketing strategy. The subscription model is revealed by the example of Netflix, which was able to turn unique content, personalization, and flexible pricing into the core of competitive advantages. At the same time, the failure of Quibi illustrates the risks of a lack of understanding of the real needs of users. The data-driven business model is vividly demonstrated by Google and Meta, which made data the main source of value creation and built multi-billion dollar advertising businesses. The opposite example of Nokia shows the consequences of ignoring the potential of analytics. The IoT model, which combines physical products with digital services, has been successfully implemented by John Deere and Philips. At the same time, the failure of Google’s Nest Secure highlights the importance of proper positioning and clear marketing communication. The Direct-to-Consumer model is illustrated by the case of Nike Direct, where the company built direct relationships with consumers based on community marketing and personalization, minimizing dependence on intermediaries. Thus, the harmonization of business models and marketing strategies in the digital economy becomes a fundamental condition for long-term competitiveness.
Keywords: digitalization; marketing strategies; business model; entropic shifts; technological challenges; technological changes